Analysis of the Relationship between Realization of Local Revenue (Pad) and Realization of Capital Expenditure with Realization of Maintenance Expenditure in Regency / City Governments in South Kalimantan Province in 2010-2016 - Nugeraha, Eddy Harwan; Adriani, Ade; Hamdani, Hamdani (Peneliti.net, 2024)
The research